A new concept in handling news source material - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The World Press Centre (WPC), based m London, is a new electronic clearing house for press material. Subscribing journalists can access on their screen any news release, briefing paper, report, announcement, profile, or feature relevant to their...